2020
DOI: 10.1038/s41415-020-1987-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dentists' professional behaviours reported in United Kingdom newspaper media

Abstract: Reporting of dental professional behaviours juxtaposes issues of crime, immoral behaviour and dishonesty with dentists' professional standing. Cases reported in the news are often sensationalist, unusual and do not appear to reflect fitness to practise cases heard by the General Dental Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A recently published article discusses how dentists' behaviour is portrayed in newspapers in the UK and found that it is often sensationalised and focused on immoral or dishonest behaviour. 1 There has always been a view from those cynical of the press that the stories are designed to have 'click-bait' titles and stories to entice the readers. Unfortunately, even with this cynicism, people can be swayed and form opinions based on the stories published.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published article discusses how dentists' behaviour is portrayed in newspapers in the UK and found that it is often sensationalised and focused on immoral or dishonest behaviour. 1 There has always been a view from those cynical of the press that the stories are designed to have 'click-bait' titles and stories to entice the readers. Unfortunately, even with this cynicism, people can be swayed and form opinions based on the stories published.…”
Section: Introductionmentioning
confidence: 99%